2020
DOI: 10.1109/access.2020.3002767
|View full text |Cite
|
Sign up to set email alerts
|

Two-Octave Supercontinuum Generation of High-Order OAM Modes in Air-Core As₂S₃ Ring Fiber

Abstract: In this work, we design and simulate an air-core As2S3 ring fiber for high-order orbital angular momentum (OAM) supercontinuum generation. We show that the chromatic dispersion of the ring fiber can be substantially tailored by proper optimization of the air-core radius. Two-octave supercontinuum carrying OAM17,1 mode, spanning from 1560 to 6250 nm, is obtained by pumping a 50-fs 100-kW secant hyperbolic pulse centered at the wavelength of 3800 nm into the designed fiber with 50-μm air-core radius and 1-μm rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Due to the huge ERID between air and the annular transmission layer, OAM can be confined to the transmission layer, so ACF has received extensive attention [23,[72][73][74][75][76]. The ACF proposed by Gregg et al [72] can support up to three high-order MGs (|l| 7, 8, 9), and a large ERID is produced between different OAM modes.…”
Section: Refractive-index-profile-modulated Rcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the huge ERID between air and the annular transmission layer, OAM can be confined to the transmission layer, so ACF has received extensive attention [23,[72][73][74][75][76]. The ACF proposed by Gregg et al [72] can support up to three high-order MGs (|l| 7, 8, 9), and a large ERID is produced between different OAM modes.…”
Section: Refractive-index-profile-modulated Rcfmentioning
confidence: 99%
“…Brunet et al [73,74] added a low refractive index layer to the conventional ACF to increase the number of supported OAM modes, which can support up to 28 OAM modes for transmission. Wang et al [23,76] used As 2 S 3 as the material of the ring transmission layer in ACF, and the ERID between the transmission ring and the air hole was higher than that of the traditional ACF. Proposed fiber can support 1004 OAM modes in all O, E, S, C and L bands.…”
Section: Refractive-index-profile-modulated Rcfmentioning
confidence: 99%
“…S. Ramachandran, et al experimentally demonstrated that ring-core ber can generate and propagate OAM modes over long distance with unprecedented stability in 2009 19 . Recent report has shown that > 1000 informationcarrying OAM states can be supported in an arsenic trisul de ring ber with air ber core 20 , and highly coherent two-octave-spanning OAM spectral broadening could be formed 21,22 . Silica (SiO 2 ) has been widely used in manufacturing optical ber by the industry and research for decades due to its favorable properties and mature preparation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reach and stability of OAM mode propagation in the ring fiber can potentially provide an effective avenue for a host of different applications. In our previous research, an air-core As2S3 ring fiber is introduced for supporting numerous OAM modes [29] and OAM supercontinuum generation [30], [31], which is promising but challenging because the complex fabrication procedure. Compared to using As2S3 as high-index ring region, Ge-doped glass is more frequently used core material of telecommunication optical fiber, as its many excellent physical properties are close to silica glass.…”
Section: Introductionmentioning
confidence: 99%